Characterization of different 5′‐untranslated exons of the ASIP gene in black‐and‐tan Doberman Pinscher and brindle Boxer dogs. (24th April 2012) - Ciampolini, Roberta; Cecchi, Francesca; Spaterna, Andrea; Bramante, Assunta; Bardet, Sylvia M.; Oulmouden, Ahmad
Summary Differential expression of the ASIP gene and its interaction with MC1R have provided basic insight into pigment‐type switching in mammals. Here, we report the characterization of a specific red‐haired skin transcript and a specific black‐haired skin transcript in the ASIP gene in the black‐and‐tan Doberman Pinscher. It is also shown that the brindle‐haired skin of the Boxer exhibits a deregulated expression resulting in various 5′‐untranslated exons. Comparative sequence analysis revealed a short interspersed element and a poly(A) stretch inserted within the promoter region of the ASIP in the Boxer. Genotyping studies have shown that both insertions are also present in brindle and fawn animals of the Boxer and Great Dane breeds. Furthermore, we genotyped MC1R and K loci for their known variants that affect coat color in dogs. As expected, all animals were homozygotes (EM/EM) for the mask mutation, and fawn animals were ky/ky. Unexpectedly, we found that all brindle animals were heterozygotes kB/ky. Our results suggest that differential expression of ASIP determine pigment‐type switching in a MC1R and K allele‐dependent manner in dogs.